Phytochemical profiling and seasonal variation of essential oils of three Callistemon species cultivated in Egypt - Gad, Haidy A.; Ayoub, Iriny; Wink, Michael (PLOS ONE, 2019)
The genus Callistemon comprises evergreen shrubs or small trees, widely cultivated as ornamentals and for essential oil production. Callistemon is well-recognized in folk medicine for its anti-cough, anti-bronchitis, and insecticidal activities. In the current study, we profiled the essential oil composition of the leaves of C. citrinus, C. rigidus and C. viminalis (Myrtaceae) collected during different seasons by GLC-MS coupled to multivariate data analysis. Antioxidant, anti-inflammatory and anti-proliferative activities of Callistemon essential oils were evaluated. A total of 29 compounds were tentatively identified. Oxygenated monoterpenes dominated in essential oils, where eucalyptol represented the major constituent in the three Callistemon species in all seasons. Multivariate data analysis including Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA) were applied to discriminate between different Callistemon species in each season and to investigate any correlation between the metabolic profile of each species within different seasons. As expected, PCA plot could discriminate the three Callistemon species in the four seasons. The dendrogram from HCA confirmed the results of PCA as it showed the same segregation pattern regarding the discrimination of different Callistemon species. C. viminalis showed more pronounced antioxidant activity than C. citrinus, exhibiting IC50 values of 1.40 mg/mL and 1.77 mg/mL, respectively. Meanwhile, C. rigidus showed very weak antioxidant activity. All oils showed membrane stabilization activity in hypotonic solution induced haemolysis assay, where C. viminalis showed potent membrane stabilizing activity exhibiting IC50 value of 25.6 μg/mL comparable to that of the standard drug, indomethacin (17.02 μg/mL). Nevertheless, Callistemon essential oils were not cytotoxic in HCT-116 and Hela human cancer cell lines.